A Systematic Literature Review on the Academic and Athletic Identities of Student-Athletes - Steele, Andrea; van Rens , Fleur; Ashley, Rebecca (Journal of Intercollegiate Sport, 2020)
Academic and athletic identities are related to performance and wellbeing indicators in both the educational and sport domains, respectively. This paper presents a systematic literature review examining empirical research into the academic and athletic identities of student-athletes in dual (education and sport) careers. The 42 records identified in this review suggest that research on the academic and athletic identities of student-athletes has focused on the themes of: identity development, role conflict, career development and motivation, and student-athlete stereotypes. Future research directions are considered, including the need for mixed-methods and longitudinal assessments of academic and athletic identities to assess to dynamic nature of identity development, and to ascertain how these relate to future performance and wellbeing outcomes.